Using wildlife indicators to facilitate wildlife monitoring in hunter-self monitoring schemes. (October 2019) - Marrocoli, Sergio; Nielsen, Martin Reinhardt; Morgan, David; van Loon, Tom; Kulik, Lars; Kühl, Hjalmar
Highlights: We tested the accuracy of wildlife indicators in a hunter self-monitoring schemes. Indicators were correlated between hunting and camera trapping methods. Indicators responded predictably to hunting pressure. Indicators correlated with species abundances and total biomass of wildlife populations. Wildlife indicators can be useful in hunter self-monitoring schemes. Abstract: Wildlife populations in tropical forests are difficult to monitor. Hunter self-monitoring schemes hold promise, but their accuracy in estimating populations has not been verified and obtaining useful wildlife estimates from generally low-quality data remains a challenge. We tested whether wildlife indicators could be useful for wildlife monitoring in such schemes, because they might eliminate the need to estimate effort in hunter surveys, and reduce records of many species into a single informative indicator. We implemented a hunter self-monitoring scheme in eight villages in the northern Republic of Congo, collecting shotgun, snare, and camera trap records in "zones" within each village's hunting territory (shotguns = 83 zones, snares = 50 zones, cameras = 21 zones). Using each of these three survey methods, we calculated for each zone three different indicators used in wildlife studies: mean body mass, the mean intrinsic rate of increase ( r max), and a duiker index (small duikers as a percentage of small and medium sized duikers). Survey effort could be estimated for both snares and cameras and was used to estimate species relative abundances (Catch Per Unit Effort, CPUE). Mean body mass was the most effective indicator, followed by the duiker index. Both were correlated between survey methods and changed with increasing hunting pressure regardless of survey method used. They also predicted the total CPUE of animals >15 kg for zones, and often the CPUE of individual species. They also gave the most precise estimates of the three indicators, and snare estimates were more precise than shotgun. In contrast, mean r max generally performed poorly, and was often not correlated with the other indicators, or with hunting pressure. Our findings suggest that some indicators can produce useful wildlife estimates from hunter self-monitoring schemes, that are also easy to implement and comprehend for hunters and wildlife managers.